Early Grade Social Studies Learning in the Independent Curriculum - Moch Fitran Naufaldy; Putri Khairunnisa; Sofian Putri Lumban Gaol; Tin Rustini (Penerbit Hellow Pustaka, 2024)
The Basic Education curriculum in Indonesia is now growing. Along with the development of technology, the learning curriculum in schools is changed to an independent curriculum where this independent curriculum is a curriculum reform that is motivated by the development of science and technology during the Covid-19 pandemic that must be implemented. The implementation of this IPAS learning is a combination of science and social studies learning. This independent curriculum gives freedom to teachers or students, and the assessment of science and social studies is united into IPAS, such as the rapport assessment which becomes IPAS. The method in this research uses qualitative with a literature review approach. The results of this literature review are that the Merdeka Curriculum in learning IPAS in the early grades also integrates the content of science and social studies subjects, teaches subject content alternately or in parallel, and uses methods and media in accordance with the independent curriculum textbook.